PERAN PENYULUHAN DALAM PEMBERDAYAAN PETANI KELAPA SAWIT POLA SWADAYA DI DESA SUNGAI BULUH KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Hasibuan, Febrian '; Sayamar, Eri '; Yulida, Roza ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purposes of this research are : (1) To identify the role of extension on oil palm independent smallholder farmers; (2) To know empowerments level of the farmers (3) To analyse the relation between extension’s role and empowerment of the farmers in Village Sungai Buluh . This research was conducted in Village Sungai Buluh sub-district Singinggi Hilir Kuantan Singingi Regency. Research’s samples was determined by purposive sampling methods by consideration that the location has active extension activities and has farmers group. The sample number are 60 the farmers. Validity and reliability analysis has been done on the measuring instruments. Data’s analysis to acknowledge the first and second research purpose used Scale Likert’s summated Rating (SLR), whereas Spearman Rank Correlation was used to acknowl edge the third purpose of this research. The Result showed that: (1) Extension has been instrumental in the oil palm farming activity pattern is seen from the variable self-education, dissemination, facilitation, consultation, supervision, and monitoring and evaluation; (2) The level of empowerment of farmers as a whole has been powerless in empowering smallholders self pattern, consisting of variable human resources, productive economic and institutional power is in the category; (3) Relationship counseling role towards the empowerment of smallholders patterns that are in the self-help level is quite strong, powerful and significant. Keywords: extension’s role, empowerments, independent smallholder farmers, palm oil